Anti-Inflammatory Effects of Lagerstroemia ovalifolia Teijsm. & Binn. in TNFα/IFNγ-Stimulated Keratinocytes. (9th November 2021) - Lee, Han-Sol; Paik, Jin-Hyub; Kwon, Ok-Kyoung; Paryanto, Imam; Yuniato, Prasetyawan; Ryu, Hyung Won; Choi, Sang-Ho; Oh, Sei-Ryang; Han, Sang-Bae; Park, Ji-Won; Ahn, Kyung-Seop
Abstract : Ethnopharmacological Relevance . Atopic dermatitis is a chronic inflammatory skin disease. Lagerstroemia ovalifolia Teijsm. & Binn. (LO) has traditionally been used as an herbal medicine for anti-inflammatory diseases. The effect of LO on atopic dermatitis has not been verified scientifically. We investigated the effects of CHCl3 fraction number 5 of LO (LOC) on atopic dermatitis through cell-based experiments. HaCaT cells were treated with tumor necrosis factor-alpha (TNF α )/interferon-gamma (IFN γ ) to induce an inflammatory reaction. Proinflammatory cytokines, interleukin- (IL-) 6, IL-8, and IL-1 β and chemokines such as thymus and activation-regulated chemokine (TARC/CCL17), monocyte chemoattractant protein 1 (MCP1/CCL2), and macrophage-derived chemokine (MDC/CCL22) were measured by RT-PCR and ELISA. In addition, the degree of phosphorylation and activation of JAK/STAT1, PI3K/AKT, and nuclear factor-kappa B (NF- κ B) were measured by western blot and luciferase assays. The production of inflammatory cytokines and chemokines and activation of the JAK/STAT1, PI3K/AKT, and NF- κ B pathways were induced by TNF α /IFN γ in HaCaT cells. Under these conditions, LOC treatment inhibited the production of targeted cytokines and chemokines and decreased the phosphorylation and activation of JAK/STAT1, PI3K/AKT, and NF- κ B. These results suggest that LOC reduces the production of proinflammatory cytokines and chemokines by suppressing the JAK/STAT1, PI3K/AKT, and NF- κ B pathways. Therefore, LOC may have potential as a drug for atopic dermatitis.